Reply to: Data do not support large-scale oligotrophication of terrestrial ecosystems. - Craine, Joseph M. (2019)
Hiltbrunner et al. apply a reductionist approach to argue that the evidence for widespread terrestrial oligotrophication2 should be replaced with a two-factor explanation (growth dilution and depositional signatures) that does not invoke reductions in N availability, that is, the supply of N relative to plant demand. Contrary to any “adjustment of leaf photosynthetic capacity and a widening of leaf C:N ratios,” there is little evidence that observed declines in foliar [N] are caused solely by photosynthetic downregulation. Photosynthetic downregulation is not universal and probably could be caused by reduced N availability. A comprehensive synthesis of data on responses of plant productivity and N acquisition to elevated CO2 in free-air carbon dioxide enrichment (FACE) experiments demonstrated that there were declines in N uptake in low-N ecosystems as a result of decreased ‘access’ to N, not reduced demand4. The growth dilution hypothesis was ‘refuted’ as an explanation for these declines.